Guinea Bissau : Qualitative Assessment of Demand Side Constraints to Access Maternal and Child Health Services - World Bank (World Bank, Washington, DC, 2019)
The objective of this research is to identify the main social and cultural constraints in accessing reproductive, maternal, newborn and child health Services (RMNCHS) in Guinea-Bissau, to effectively improve their access and use by women and children. Additionally, the research also explores aspects related to female genital cutting (FGC or FGM) and girls’ access to information on reproductive health. The demand barriers to improve access and coverage of quality of MCH services were previously listed as: (i) poor technical quality, (ii) poor responsiveness; (iii) high controversial costs; (iv) access/distance to health facilities; (v) use of traditional practices. These intertwine with supply side barriers such as: (i) weakness of training capacity; (ii) shortage of health professionals; (iii) inadequate referral system; and (iv) weak supply chain. Six major themes were researched and outlined in this paper: (i) use of health facilities (ante-natal care and delivery at home/health center (HC), women´s secrets and men’s, elderly women and the kingdom of the health center); (ii) access to health facilities (distance, transportation); (iii) the health center (staff competence, payments/gratuities, possible improvements); (iv) socio-cultural issues (gender, religious); (v) reproductive health and FGM (family planning); (vi) health staff: community health agent (CHA) (being a CHA, access to the health center, relationship with the HC and with the community, socio-cultural issues, reproductive health and FGM); and (vii) health staff: nurses (being a nurse, access to the health center, relationship with the community, socio-cultural issues, reproductive health and FGM).